1998
DOI: 10.1103/physrevlett.80.4931
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Surfactant Mediated Growth of Ge on Si(001)

Abstract: The role of hydrogen in the growth of Ge on a Si͑001͒-͑2 3 1͒ surface was studied by scanning tunneling microscopy and medium energy ion scattering spectroscopy. The adsorbed hydrogen was found to (i) increase the number of equilibrium adsorption sites, (ii) lift the diffusion anisotropy, and (iii) lower the diffusivity for Ge adatom, as suggested by the recent first principle calculation. With a dynamically supplied atomic hydrogen flux of ϳ2 monolayers͞s, we achieved layer-by-layer growth by preventing growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…On H-terminated surfaces, the S B steps are nonrebonded, and attaching a Si adatom to the step edge is tantamount to converting it to a higherenergy rebounded step. This simple mechanism could also account for similar effects of hydrogen on Ge and SiGe film growth [49][50][51], and may explain the suppression of Co and Ni silicide formation on H-terminated Si [52][53][54]. Similarly, our results may explain the spontaneous step formation observed on Si(0 0 1) annealed in H 2 under extreme conditions ($1 atm, 1200°C) [55].…”
Section: Discussionsupporting
confidence: 68%
“…On H-terminated surfaces, the S B steps are nonrebonded, and attaching a Si adatom to the step edge is tantamount to converting it to a higherenergy rebounded step. This simple mechanism could also account for similar effects of hydrogen on Ge and SiGe film growth [49][50][51], and may explain the suppression of Co and Ni silicide formation on H-terminated Si [52][53][54]. Similarly, our results may explain the spontaneous step formation observed on Si(0 0 1) annealed in H 2 under extreme conditions ($1 atm, 1200°C) [55].…”
Section: Discussionsupporting
confidence: 68%
“…MEIS provides both compositional and structural information with atomic layer depth resolution through analyses of energy and angular distributions of elastically scattered protons. 11,12 The strain depth profiles we obtain clearly show that Ge layers consisting entirely of pyramids exhibit a uniform in-plane compressive strain ʈ of 2.1%, while dome-dominated Ge/Si͑001͒ surface morphologies exhibit a large gradient in ʈ ranging from 0.6% at the outer surface to 2.1% at the Ge/Si͑001͒ interface.…”
mentioning
confidence: 93%
“…It has been shown that surfactants dramatically suppresses the Ge island formation and promotes layer-by-layer Ge growth: [7][8][9] under the hydrogen-surfactant epitaxy, Ge islanding does not occur and the strain-relaxed Ge film grows on Si substrate. 8,9 In these Ge/Si͑001͒ heterostructures, the 90°e dge dislocation with the Burgers vector along the ͗110͘ direction is observed near the Ge/Si interface.…”
Section: Introductionmentioning
confidence: 99%